Can nudging improve the environmental impact of food supply chain? A systematic review. (September 2019) - Ferrari, Linda; Cavaliere, Alessia; De Marchi, Elisa; Banterle, Alessandro
Abstract: Background: According to the prediction of the Food and Agriculture Organization, food supply must increase by almost 70 percent by 2050, with tremendous consequences in terms of land depletion, natural resource use, and greenhouse gas emissions. The currentagri-food system is incapable to cope with this raising demand meanwhile preserving the environment. There is urgent need to reorient the food system onto a more sustainable trajectory: producers should pursue more conscious and environmentally friendly practices and consumers should account forsustainability issues while making their daily food consumption decisions. Scope and approach: The goal of thissystematic review is to gather existing evidence ongreen nudging interventions geared at leveraging more environmentally sustainable behaviours among the agents of the food chain, from the producers to the final consumers. An extensive literature search was conducted on Web of Science, Scopus, EconLit, and CAB Abstracts, restricting the selection to the last ten years, and using "nudg*" or "choice architecture" as primary research strings. Finally, 25 studies were included in the review. Key finding and conclusions: Almost all studies on farmers as well as on consumers included in this review provide evidence that green nudging can be effective in leveraging more sustainable practices. Overall, we propose that green nudges should not be meant to replace stricterenvironmental and foodpolicies, but rather they should be regarded as potential complements to be implemented with the aim of gradually moving society in a direction that might benefit all. Highlights: The agri-food system is unable to satisfy the raising food demand in a sustainable way. There is urgent need to reorient the food system onto a more sustainable trajectory. Policies based on green-nudging may be a promising way to address sustainability goals. Green nudging can leverage sustainable behaviours among the agents of the food chain. Green nudges can contribute to move firms and consumers towards sustainable behaviors.